1994
DOI: 10.1364/josaa.11.000487
|View full text |Cite
|
Sign up to set email alerts
|

Lower-field myopia and astigmatism in amphibians and chickens

Abstract: In some afoveate vertebrates refractive state appears to vary over the eye to match the average viewing distances of different areas of the visual field. However, precise measurements are difficult to obtain even in anesthetized animals, because standard methods of refraction are not designed for off-axis measurements and because the presence of astigmatism may fog the results. Therefore we developed a new automated objective technique, automated infrared photoretinoscopy, and measured off-axis refractions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 15 publications
3
43
0
Order By: Relevance
“…39 Studies in amphibians have shown that fluctuations in astigmatism, correlated with changes of the refractive power along the vertical meridian, are particularly prevalent in the ventral visual field. 40,41 The mechanism underpinning astigmatism in the ventral field is not understood, although astigmatism is induced by the corneal surface, in which the curvature tends to decrease from dorsal to ventral aspects. VAX2 also plays an important role in controlling retinoic acid (RA) metabolism in the developing eye in vertebrates, particularly in maturation of the retina, 42 but RA is also involved in development of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…39 Studies in amphibians have shown that fluctuations in astigmatism, correlated with changes of the refractive power along the vertical meridian, are particularly prevalent in the ventral visual field. 40,41 The mechanism underpinning astigmatism in the ventral field is not understood, although astigmatism is induced by the corneal surface, in which the curvature tends to decrease from dorsal to ventral aspects. VAX2 also plays an important role in controlling retinoic acid (RA) metabolism in the developing eye in vertebrates, particularly in maturation of the retina, 42 but RA is also involved in development of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were mounted into a stereotactic apparatus and the eyes were focused on the stimulus screen (24 inch LCD monitor, gamma corrected, Belineao.display 4.1, Belinea; refresh rate, 70 Hz)-placed 50 cm in front of the animals' eyes-by using PMM contact lenses (Soflex Israelens Contact Lenses Ltd.) and an infrared video refractor (Schaeffel et al, 1994;Troilo et al, 2007). The stimulus screen spanned 55°horizontal ϫ 37.5°vertical of the animal's central field of view.…”
Section: Methodsmentioning
confidence: 99%
“…Maintenance of constant velocity is likely to facilitate accurate path planning and robustly stable running in uneven terrain. Birds also have lower-field myopia (near-sightedness), allowing them to keep the ground in focus at eye height with the upper field focused at distances (Hodos and Erichsen, 1990;Schaeffel et al, 1994), enhancing their ability to dynamically gauge terrain. The results of the present study suggest that birds use visual route planning when presented with sufficient visual information.…”
Section: The Role Of Vision In Route Planning For Obstacle Negotiationmentioning
confidence: 99%